DOCTOR-PATIENT INTERACTION: A SYSTEMIC FUNCTIONAL ANALYSIS - Isli Iriani Indiah Pane; Amrin Saragih; Nurlela Nurlela; Masdiana Lubis (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
One of the basic mediums in the interaction between doctor and patient in the treatment room is language. This paper, hence deals with the conversation in doctor-patients interaction in Pirngadi General Hospital in Medan, Indonesia. Clauses in the conversations were adopted as the main research data. The analysis is based on the theory of Systemic Functional Linguistics pioneered by Halliday (2004). The research was conducted by applying top-down approach from the analysis of the consultation in terms of context of situation that is concerned with register variables covering field, tenor and mode. Then, the analysis further focuses on the experiential function in terms of transitivity system covering the analysis of the processes used the participant functions involved and the interpersonal function covering mood and modality. The study was conducted by using descriptive qualitative method with triangulation. It refers to the use of multiple methods or data sources in qualitative research to develop a comprehensive understanding of phenomena. Triangulation is viewed as a qualitative research strategy to test validity through the convergence of information from different sources. The results of the analysis have revealed that social relation exists in the language used by the doctor and the patient in their interaction in which the doctor has more power over the patient.